Implementasi Program Tahfidz Al-Qur’an dalam Menumbuhkan Karakter Religius Siswa di SMP Nahdlatul Ulama’ Karanggeneng - Khoirun Nisak, Amelia; Lathifatus Sun'iyah, Siti; Ashrofun Nashr, M. Naqouib (Fakultas Agama Islam, 2025)
Memorizing the Qur'an is a great act of worship before the creator, namely Allah SWT. In addition, memorizing the Qur'an is not only called memorizing the Qur'an, but can also be used to grow and develop the religious character of every human being. So in this case, the tahfidz al-Qur'an program has a very significant impact on the formation of student character. The objectives of this study are: (1) to determine the implementation of the tahfidz al-Qur'an program at SMP Nahdlatul Ulama'Karanggeneng (2) to explore the Tahfidz Al-Qur'an program in growing the religious character of students at SMP Nahdlatul Ulama' Karanggeneng. This research uses a descriptive qualitative research method by conducting in-depth interviews with several teachers and students of the Al-Qur'an memorization program (tahfidz), as well as participatory observation at the SMP NU Karanggeneng school. Data analysis is carried out through data collection, data reduction, data presentation, and drawing conclusions. Based on the research results, it is found that the implementation of the Al-Qur'an memorization program in fostering the students' religious character at SMP Nahdlatul Ulama Karanggeneng involves several methods, namely the juz’i method, the tasmi’ or test method, the muroqobah method, and the muraja’ah or takrir method. Furthermore, this tahfidz program has a positive impact on the students' religious character, particularly in their worship practices and daily behavior